A breath of snow and ashes [compact disc, unabridged] - Gabaldon, Diana (Gabaldon, Diana. Outlander novels., 2005)
In the sixth installment of Diana Gabaldon's acclaimed Outlander series, 20th century time traveler Claire Fraser reveals some unsettling news to her 18th century husband, Jamie, on the eve of the American Revolutionary War. Slated to die according to a 1776 obituary, Jamie attempts to change his fate. However, many of the Frasers' friends are divided on opposite sides of the war, putting Jamie's life in perpetual danger.